Physical Water Flow Accounts as a Part of European Environmental Economic Accounting - Rosiek, Ksymena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
Water is a crucial resource that ensures life on the planet. It is defined as a replenishable but depletable resource, so it is necessary to manage it and define the rules and boundaries of its usage among competing users. To ensure sustainable water resource use, it is necessary to create sophisticated statistical tools that can provide information about the relations between economy and the environment. Basing them on coherent definitions and the national accounts nomenclature is of utmost importance.This article concerns aspects of economic environmental accounting that are still not obligatory in the EU, though they are practiced, and intensively so, both in the EU and further afield. It can be expected that they will be included in the next obligatory modules of ESEA, which are to be introduced soon.